Aspek-aspek Pengembangan Pendidikan Sosio-kultural dalam Keluarga Muslim - Asri Andika Amalia; Raisya Miftakhul Rahma (EL-TARBAWI, 2022)
Education is essential for humans in facing the complex life. In Islam, the first education starts from the family. The family is the initial environment that forms and grows individual personality through habitual instillation by parents. The purpose of this research is to discuss Islamic religious education in the family through a socio-cultural perspective. The method used by researchers is library research method by collecting literature sources from books, journals, and other related articles. This study found that the development of sociocultural education in Muslim families can be carried out through three aspects, helping each other, community unity and brotherhood of community. In constructing these socio-cultural values, parents play an important role in providing exemplary education, habits, advice, attention, rewards and punishments for children in accordance with Islamic law.